PERLINDUNGAN DAN TANGGUNG JAWAB OTORITAS JASA KEUANGANTERHADAP DATA KONSUMEN DALAM TRANSAKSI PINJAMAN ONLINE - Dini Kartika Sari (2022)
Legal protection and sanctions for personal data breaches have been regulated in Law no. 11 of 2008 and its amendments regarding Information and Electronic Transactions, but specifically regarding legal protection and sanctions for personal data violations in online loan services have been regulated in Financial Services Authority Regulation Number 77/POJK.01/2016 concerningInformation Technology-Based Loans and Lending Services, which it is emphasized in Article 26 that the operator is responsible for maintaining the confidentiality, integrity and availability of theuser's personal data and its use must obtain approval from the owner of the personal data unless otherwise stipulated by legal provisions. The problem in this study is regarding the disseminationof personal data by online loan providers without notification and without permission from the owner. The purpose of this paper is to examine the legal protection of borrowers' personal data inonline loan application services. The method used in this paper is a normative legal method with a statutory approach and a case approach. The results of this study are sanctions for violating personal data referring to Article 47 paragraph (1), namely administrative sanctions in the form of written warnings, fines, obligation to pay a certain amount of money, restrictions on business activities, and revocation of permits. The role of OJK as an institution that oversees financial service institutions other than banks has not been maximized, so it is necessary to make arrangements to prevent misuse of debtor's personal data and socialize to the public about legal and illegal online loan service companies.